HUBUNGAN ANTARA COPING EFFORT DENGAN UPAYA MENCARI KESEMBUHAN PENYALAHGUNA NARKOBA JARUM SUNTIK - Oktavian Denis Hartanto; Mochammad Bagus Qomaruddin (Universitas Airlangga, 2016)
Injection drug user can be the gateway of various disease transmission such as hepatitis andHIV - AIDS. Many of injection drug users did therapy, but in fact there are still users who return to usedrug called recurrence or relapse. An important factor to help and save the drug users in order to getrid of the addicted is coping eff ort consisted of problem management and emotional regulation.The aimof this study was to fi nd out the relationship between coping eff ort with the eff ort of injection drug usersto recover theirself in Surabaya Orbit Foundation. This study used an observational study design andcross sectional study. The sample of this research determined by simple random sampling. Informationobtained through the questionnaire that read to the 34 respondents. The majority of respondents inthe study is male and work as a private employee, especially in the drugs area. Respondents aged areproductive and follow therapy 1–5 years. Respondents have a good coping eff ort and very good in anattempt to recover theirself from drug addicted. The results showed the value of p = 0,001 and r = 0,546.There is strong relationsip between coping eff orts and the eff ort of injection drug users to recovertheirself in Surabaya orbit foundation.Keywords: IDU, recover theirself, coping